MENINGKATKAN INTERNALISASI USAHA MELALUI INOVASI PRODUK DAN LEGALITAS USAHA UNTUK MENCIPTAKAN KUALITAS BISNIS - Sutrisno, Sutrisno; Mustofa, Moh; Tira, Oky Oktavian Agus; Sampoerno, Tegar Rahmat (Jurnal Abdi Masyarakat, 2025)
The mentoring program for the Mambo Premium Ice Small and Medium Enterprise (SME) in Bojonegoro Regency was motivated by challenges faced in product innovation and business legality. The main problems identified were the lack of product variety and attractiveness, as well as the lack of a Business Identification Number (NIB), which limits access to market opportunities and government support. This program aims to improve the competitiveness of SMEs through the development of product innovation and business legality. The approach used needs analysis, product innovation training, and assistance with NIB processing through the OSS system. The mentoring results showed significant improvements, with partners successfully creating new product variants, such as matcha, tiramisu, and taro flavors, which increased consumer appeal. In addition, partners have obtained NIBs, opening access to government facilities and increasing consumer trust. With a structured approach, this program has succeeded in building a more professional, sustainable, and competitive business foundation in the market.